2018
DOI: 10.1001/jama.2017.21547
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for Chronic Neuropathic Pain

Abstract: Oral gabapentin (1200-3600 mg/d for 4-12 weeks) for patients with moderate or severe neuropathic pain from postherpetic neuralgia (PHN) or painful diabetic neuropathy (PDN) is associated with pain reduction of at least 50% in 14% to 17% more patients than placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 8 publications
0
34
0
1
Order By: Relevance
“…The higher rates of side-effects observed with gabapentin compared with placebo (eg, dizziness, drowsiness, and visual disturbances) in the trial are consistent with other published studies. A 2018 meta-analysis of all trials for postherpetic neuralgia and painful diabetic neuropathy 28 showed that, compared with placebo, gabapentin was associated with more drowsiness (gabapentin 14% vs placebo 5%; p<0·001) and dizziness (gabapentin 19% vs placebo 7%; p<0·001). Nevertheless, the rates of side-effects in our trial are lower than in these other studies, despite only measuring these in women.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rates of side-effects observed with gabapentin compared with placebo (eg, dizziness, drowsiness, and visual disturbances) in the trial are consistent with other published studies. A 2018 meta-analysis of all trials for postherpetic neuralgia and painful diabetic neuropathy 28 showed that, compared with placebo, gabapentin was associated with more drowsiness (gabapentin 14% vs placebo 5%; p<0·001) and dizziness (gabapentin 19% vs placebo 7%; p<0·001). Nevertheless, the rates of side-effects in our trial are lower than in these other studies, despite only measuring these in women.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, treatment with Noxiall ® elicited a marked enhancement of the withdrawal threshold in response to a mechanical stimulus applied to the ligated paw suggesting an ability of this treatment to attenuate allodynia. In parallel to treatment with Noxiall ® , a separate group of mice was treated with gabapentin, an anti-epileptic agent that is a first-line treatment for NP in the clinic (Wiffen et al, 2017; Moore et al, 2018). The dose of gabapentin used was chosen based on previous studies in which its efficacy in rodent CCI models was demonstrated (Kusunose et al, 2010; Corona-Ramos et al, 2016; Hewitt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…85 Gabapentin is associated with pain reduction in patients with moderate or severe neuropathic pain from post-herpetic neuralgia or painful diabetic neuropathy. 87 Both gabapentin and pregabalin have been used in several pediatric studies of vincristine-induced neuropathy, but their efficacy has not been unequivocally established. 80,88…”
Section: Management Of Neuropathymentioning
confidence: 99%